Features and determinants of the firm size distribution: An enpirical analysis with Brazilian data - Miguel Nathan Foguel; Eduardo Pontual Ribeiro (Institute for Applied Economic Research (ipea), 2023)
The Pareto distribution has been used to describe firm sizes in many theoretical models for its convenience and empirical validity. We provide estimates of the Pareto parameters across industries and investigate the determinants of the shape of the firm size distribution in Brazil. The Pareto tail distribution is not rejected for about 70% of the industries, with the Zipf tail distribution (scale coefficient equal to 1) accepted for about 50% of the industries. The size distributions in manufacturing and all industries are affected by the human capital intensity and may be affected by industry uncertainty and instability, in line with the literature.
Keywords: C12; D30; L10; 330; firm size distribution; Pareto distribution; human capital